PEMBELAJARAN MAHASISWA KEPERAWATAN STIKES MUHAMMADIYAH GOMBONG SELAMA PANDEMI COVID-19 - Eka Riyanti; Nurlaila Nurlaila (Universitas Muhammadiyah Surakarta, 2022)
Efforts to prevent the spread of Covid-19 were carried out by means of social distancing and self-isolation. This effort has also forced the closure of all schools, both elementary and tertiary levels. School closures were carried out in more than 100 countries. Learning during this pandemic requires STIKes Muhammadiyah Gombong to conduct online or online learning. The purpose of scientific writing is to provide an overview of the learning of nursing students at STIKes Muhammadiyah Gombong during the Covid 19 pandemic. The method used in this study is descriptive by distributing questionnaires and interviews to assess the learning process online. The Results showed that the percentage of student who Disliked online learning is 52.8%, Online learning schedule according to predefined class schedules 48.3%, Liked learning media used by online lecturers 44%, opening E Learning to better master the material 61.4%, less supportive facilities to access online learning media 40.1%, the media used by lecturers was not easily accessible and used 50.3%, online learning did not increase my learning outcomes 57.7%, difficulty understanding material in online learning was 53.4%. Recommendations are needed online learning guides and supporting facilities for the effectiveness of online learning